The Influence of Regional Debt and Capital Expenditures on Financial Sustainability in Provincial Governments in Indonesia - Cahyani, Annisa Dwi; Dewata, Evada; Mayasari, Riana (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Financial Sustainability fluctuates every year in every province in Indonesia during the 2019-2022 period, indicating an increase or decrease in the quality and quantity of public services provided to the community. This study aims to reveal that regional debt and capital expenditure have an effect on financial sustainability. The type of research conducted is associative research that applies quantitative methods, using secondary data sources and using panel data. The population in this study consists of 34 provinces in Indonesia, and the sampling method applied is saturated sampling. The research findings indicate that regional debt has a negative impact on financial sustainability, while capital expenditure has a positive effect on financial sustainability.